Inquietantes traslados: uma leitura psicanalítica do filme Encontros e Desencontros - SOUZA, Maurício Rodrigues de (2014)
In search of articulations between psychoanalysis and cultural practices – here represented by the magic of cinema - this work proposes an analysis of the movie Lost in Translation, taking it as a privileged interlocutor to a discussion about otherness. More specifically, we will focus on the possibility, present both in analytical clinics and in the movie mentioned above, of an encounter with the unspeakable of the self by the means of a stranger. It's a dialectical clash between the most intimate stranger and the strangest intimate, bounded to the primary process, to the logics of the Unconscious. Therefore, we suggest that although this non-familiarity is in general associated to an uncomfortable anguish, it is possible to consider another expression to it: that one of constructive potency towards an expansion of meaning.